Association Between Serum Carcinoembryonic Antigen Levels at Different Perioperative Time Points and Colorectal Cancer Outcomes - Li, Zhenhui; Zhang, Dafu; Pang, Xiaolin; Yan, Shan; Lei, Ming; Cheng, Xianshuo; Song, Qian; Cai, Le; Wang, Zhuozhong; You, Dingyun (Frontiers in Oncology, 2021)
Background: Whether elevated postoperative serum carcinoembryonic antigen (CEA) levels are prognostic in patients with stage II colorectal cancer (CRC) remains controversial. Patients and methods: Primary and sensitivity analysis populations were obtained from a retrospective, multicenter longitudinal cohort including consecutive patients without neoadjuvant treatment undergoing curative resection for stage I–III CRC. Serum CEA levels before (CEApre-m1) and within 1 (CEApost-m1), 2–3 (CEApost-m2–3), and 4–6 months (CEApost-m4–6) after surgery were obtained, and their associations with recurrence-free survival (RFS) and overall survival (OS) were assessed using Cox regression. Sensitivity and subgroup analyses were performed. Results: Primary and sensitivity analysis populations included 710 (415 men; age, 54.8 [11.6] years) and 1556 patients (941 men; age, 56.2 [11.8] years), respectively. Recurrence hazard ratios (HRs) in the elevated CEApre-m1, CEApost-m1, CEApost-m2–3, and CEApost-m4–6 groups were 1.30 (95% CI: 0.91–1.85), 1.53 (95% CI: 0.89–2.62), 1.88 (95% CI: 1.08–3.28), and 1.15 (95% CI: 0.91–1.85), respectively. The HRs of the elevated CEApre-m1, CEApost-m1, CEApost-m2–3, and CEApost-m4–6 groups for OS were 1.09 (95% CI: 0.60–1.97), 2.78 (95% CI: 1.34–5.79), 2.81 (95% CI: 1.25–6.30), and 3.30 (95% CI: 1.67–.536), respectively. Adjusted multivariate analyses showed that both in the primary and sensitivity analysis populations, elevated CEApost-m2–3, rather than CEApre-m1, CEApost-m1, and CEApost-m4–6, was an independent risk factor for recurrence, but not for OS. The RFS in the elevated and normal CEApost-m2–3 groups differed significantly among patients with stage II disease (n = 266; HR, 2.89; 95% CI, 1.02–8.24 [primary analysis]; n = 612; HR, 2.69; 95% CI, 1.34–5.38 [sensitivity analysis]). Conclusions: Elevated postoperative CEA levels are prognostic in patients with stage II CRC, with 2–3 months after surgery being the optimal timing for CEA measurement.